2020
DOI: 10.1088/1757-899x/736/3/032015
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of petrochemical wastewater as substrate in microbial fuel cell

Abstract: The petrochemical wastewater (PCW) from acrylic acid plant possesses very high chemical oxygen demand (COD) due to presence of acrylic acid along with other organic acids. The treatment of PCW by conventional methods is energy intensive. The treatment of PCW with concurrent power generation by employing microbial fuel cell (MFC) could be a potential alternative solving the problem of energy and environment. The goal of the present paper is to evaluate the viability of treating the wastewater using anaerobic sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Through oxidation in the MFCs systems with activated sludge, bioelectricity was generated and used in the cathode chamber [82]. The petrochemical wastewater from an acrylic acid planet with a high COD value has been investigated as a substrate for generating electricity in a dual-chamber of MFC with anaerobic sludge as a sample of BCs [83].…”
Section: Purification Processesmentioning
confidence: 99%
“…Through oxidation in the MFCs systems with activated sludge, bioelectricity was generated and used in the cathode chamber [82]. The petrochemical wastewater from an acrylic acid planet with a high COD value has been investigated as a substrate for generating electricity in a dual-chamber of MFC with anaerobic sludge as a sample of BCs [83].…”
Section: Purification Processesmentioning
confidence: 99%
“…The data obtained showed that this bacterium can produce a maximum voltage of 355 mV in MFC during the process of treating oil refinery wastewater [44]. Sarmin et al [45], conducted a study where they utilized petrochemical wastewater to generate electricity using a dual-chamber microbial fuel cell (MFC) system. The results indicated that this system was capable of producing a maximum voltage of 450 mV.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Similar to other wastewaters, it is crucial to treat petroleum wastewater with a high COD in an energy-efficient manner [ 160 , 161 ]. The efficacy of anaerobic sludge as the MFC inoculum for petroleum wastewater from an acrylic acid plant was evaluated in a double-chamber MFC [ 162 ]. The MFC shows a PD max of 0.75 W m −2 , CD max of 412 mA m −2 (after seven days), maximum output voltage of 0.45V, CE efficiency of 13.11% (after ten days), and COD removal of 40%.…”
Section: Complex Substratesmentioning
confidence: 99%
“…The MFC shows a PD max of 0.75 W m −2 , CD max of 412 mA m −2 (after seven days), maximum output voltage of 0.45V, CE efficiency of 13.11% (after ten days), and COD removal of 40%. The study demonstrates the use of anaerobic sludge-based MFC to treat petroleum wastewater [ 162 ]. In another study, petroleum refinery wastewater was used to generate electricity.…”
Section: Complex Substratesmentioning
confidence: 99%